2019
DOI: 10.1093/aob/mcz187
|View full text |Cite
|
Sign up to set email alerts
|

Daily fluctuations in pollination effectiveness explain higher efficiency of native over exotic bees in Lepechinia floribunda (Lamiaceae)

Abstract: Background Despite Stebbins’ principle of the most efficient pollinator being proposed decades ago, the most important pollinators are still mainly identified using the frequency of visits to flowers. This shortcoming results in a gap between the characterization of the flower visitors of a plant species and a reliable estimation of the plant fitness consequences of the mutualistic interaction. The performance of a mutualistic visitor depends on its abundance, behaviour, effectiveness (pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Effective pollinators usually match their activity with floral anthesis. Indeed, the performance of a visitor depends on the temporal matching between its activity and temporal patterns of reproductive maturation of the flowers [ 27 ]. We found that vanilla in the Yucatán blossoms between the end of March and mid-May, like other regions of the Northern hemisphere where it is cultivated [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective pollinators usually match their activity with floral anthesis. Indeed, the performance of a visitor depends on the temporal matching between its activity and temporal patterns of reproductive maturation of the flowers [ 27 ]. We found that vanilla in the Yucatán blossoms between the end of March and mid-May, like other regions of the Northern hemisphere where it is cultivated [ 2 ].…”
Section: Discussionmentioning
confidence: 99%